How perceptual differences between leaders and followers affect the resilience-workability relationship - Caniëls, Marjolein C. J. (Frontiers in Psychology, 2023)
Drawing on Conservation of Resources theory and its notion of resource passageways, the aim of this study is to investigate the relationship between resilience and workability, and particularly the extent in which this relationship is buffered or strengthened by differences in perception between leaders and employees about the degree in which a certain influence tactic (pressure or rational persuasion) is used. To this end we use a two-wave time-lagged survey design with a multi-sourced sample of 146 leader-follower dyads. Findings indicate that leader-follower perceptual differences about the use of pressure as an influence tactic buffers the positive resilience-workability relationship of followers. No evidence was found of a similar effect with respect to rational persuasion as an influence tactic.